The Habituation of Behavior as Students’ Character Reinforcement in Global Era - Santi Lisnawati (Jurnal Pendidikan Islam, 2016)
This study aims to investigate the implementation of students’ habituation in schools and religious attitudes which are owned by them as an effort to strengthen positive behavior in globalization era. This research was conducted at Integrated Islamic Elementary School (SDIT) Insantama Bogor. The method used is descriptive qualitative method. The results showed that the school has a number of activities, with emphasis on habituation. Habituation at school refers to the value of the Islamic teachings. Since the entry gate to home school, students familiarize positive behavior. Students have a noble character or al-akhlãk al-karîmah through habituation derived from value of Islam. The students at SDIT Insantama Bogor familiarize the positive behaviour, so that they have a noble character, such as having a character to Allah (loving Allah), behaving whole hearted, behaving honest, feeling self-confident, behaving emphatic, forgiving, saying well, behaving tolerant, and having the character towards environment by loving the nature and keeping the environment clean.